Tratamiento informativo de los temas de migración en los medios de comunicación impresos de Riobamba, 2021. - Cando Inga, Liliana Evelin (2023)
This research analyzes the informative treatment of migration issues in the printed media of the city of Riobamba in the period 2021, it arises as a response to the need to know the handling of information in the printed media, an event that afflicts the Ecuadorian society. The research is presented as descriptive, quantitative because data were collected considered as attributes of the subject investigated to identify how was the informative treatment, recognizing which were the components that were used at the time of publishing the information reaching an inference that depends on the social context where the message is issued, it also has the application of a qualitative analysis, because the news were processed to know how the news of such media are treated. Documentary research, content analysis and interviews to professional experts related to the informative topic were used as techniques, the results show that the migratory topic in the printed media has a news type treatment, with multiple sources of origin and condition of violation of rights.